Strengthening the Roles of Teachers in Educating Broken Home Students of Junior High School - Marpaung, Tiarma Intan; Purba, Christian Neni; Hutahaean, David Togi (PT FORMOSA CENDEKIA GLOBAL, 2024)
This community service aims to strengthen the role of teachers in educating students who come from broken home families in SMP Negeri 2 Siantar.This activity is beneficial for minimizing the negative activities of broken home students at school due to attracting teachers’ and other students’ attention. In this context, the teacher’s role is very important in providing a comprehensive education to students and helping them overcome challenges related to their family conditions. This article highlights some of the major roles that teachers can play in educating broken home students, including creating a safe learning environment, providing emotional support, developing social and emotional skills, and collaborating with parents and other professionals to provide the right kind of attention to these students.